1993
DOI: 10.1002/mus.880160908
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine alters apamin receptors, electrical activity, and skeletal muscle relaxation

Abstract: A low conductance calcium-activated K+ channel is thought to regulate the rate of firing of several excitable cells. In skeletal muscle the expression of this channel is under nerve control. Previously, we reported that axonal flow blockade of rat nerves, induced by colchicine, caused a transient increase in muscle apamin receptors, determined by 125I-apamin binding to membrane fractions. The increase in apamin receptors was correlated with repetitive discharges resembling myotonic potentials in the electromyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Application of the bee venom peptide toxin apamin, a blocker of SK channels, dramatically reduces the hyperexcitability of denervated muscle, 44 implicating SK channels in the genesis of the hyperexcitability. The experiments presented here investigated the molecular basis for SK channel-mediated skeletal muscle hyperexcitability following denervation or in cultured muscle cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of the bee venom peptide toxin apamin, a blocker of SK channels, dramatically reduces the hyperexcitability of denervated muscle, 44 implicating SK channels in the genesis of the hyperexcitability. The experiments presented here investigated the molecular basis for SK channel-mediated skeletal muscle hyperexcitability following denervation or in cultured muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular basis for the hyperexcitability is not yet understood, these conditions share an important property: the tissue contains receptors for the bee venom peptide toxin apamin, a blocker of small-conductance calciumactivated potassium (SK) channels, and apamin application reduces or abolishes the hyperexcitability, 10,38,44 suggesting that SK channels are central to the genesis of the hyperexcitability.…”
mentioning
confidence: 99%
“…It was indeed observed that following axoplasmic Xow blockade, as well as nerve section, the number of apaminesensitive calcium activated K + channels-whose level is negligible in innervated muscles-increases, with an increase of muscle Wber excitability which might be related to Wbrillation activity (Behrens and Vergara 1992;Ramirez et al 1996;Vergara et al 1993). Direct application of colchicine to the muscle did not alter the channel expression, while histological examination of the nerve showed no signs of nerve lesions (Behrens and Vergara 1992).…”
Section: Other Experiments Which Might Suggest a Neurotrophic Controlmentioning
confidence: 92%
“…ThesleV and Ward (1975) suggested that normal levels of calcium ions in denervated muscle are less eVective as membrane stabilizing agents, which should favor membrane spontaneous activity, and a role of cytosolic calcium in the genesis of Wbrillation has been proposed by Brodie (1966) and Izumi et al (1998). The occurrence of Wbrillation has also been related to the increase of a particular kind of low conductance, Ca 2+ -activated K + channels after denervation, with a resulting increase of excitability of muscle Wber membrane (Vergara et al 1993) (see also "Extrajunctional membrane properties" section). Quite recently, in light of the results obtained with in vitro myogenesis, it was proposed that Wbrillation is related to the autocrine activation of AChRs in muscle Wber membrane (Bandi et al 2005).…”
Section: Fibrillation Activity Of Denervated Musclementioning
confidence: 94%
“…At low doses, their topical application can effectively block axoplasmic transport in both myelinated and unmyelinated axons without causing axonal damage (< 10 m m for colchicine: Jackson & Diamond, 1977; Tiedt et al . 1977; Vergara et al . 1993; Kingery et al .…”
mentioning
confidence: 99%